Improvement of livelihood, food and nutrition security through homestead vegetables production and fruit tree management in Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
Sustainable, safe and nutritious food productions are the major challenges for global food security which meets dietary needs and food preferences for an active and healthy life. The objectives of the study were to utilize homestead resources in scientific method for producing fresh vegetables and fruits over space and time and to meet up the food and nutritional security of the farmers. Household survey was carried out to ascertain livelihoods information of the selected farm households before intervention. The trial was conducted at six replications by the participatory approaches following vegetables production Golapgonj Model. Results revealed that a family consisting five members having small homestead area with some fruit trees could be capable of harnessing sufficient and diversified vegetables and fruit round the year by utilizing the all possible homestead nieces and management of fruit trees. Results also suggested that the farmers consumed lion share of their products that could meet up nutrition from various vegetables and fruits, some of them distributed a portion to relatives and neighbors and also sold a portion of them. The additional income generated by selling of surplus vegetables and fruits was generally utilized to purchase supplementary food items, in turn increase the diversification of the familys diet. Interestingly, active participation of family members (especially women and children) in their homestead vegetable production activities was also ensured. Thus, all these might be lead to full utilization of both physical & other farm resource available in the farm & mobilize resources that increased food & nutritional security, income as well as improved their livelihoods as well.J. Bangladesh Agril. Univ. 12(2): 377-387, December 2014